The regulation of shadow banking in South Africa and proposals for reform based on the United States and China experience - Narendrecumar, Nipa (My University, 2019)
Over the years, shadow banking has experienced a significant increase within the global financial system, with the United States (US) having the largest shadow banking sector. Emerging economies, particularly China have also seen a significant increase in shadow banking activities. Following the global financial crisis of 2007–2008, there have been concerns over the risks that are posed by shadow banking and the need for regulation of the sector. Consequently, the aim of this research report was to assess the regulation of shadow banking in South Africa and to make proposals for reform based on the experiences of the US and China. The findings show that shadow banking, while useful to the economy, poses systemic risks to the financial system. In the US, shadow banking is widespread, and had a significant impact in exacerbating the effects of the global financial crisis. Consequently, major reforms were put in place to reduce these risks through the Dodd-Frank Act and the Consumer Protection Act. The report also shows that the Chinese financial system has undergone major reforms. Due to the inadequacies of the financial system in offering credit, shadow banking has risen significantly in China amid concerns over a poor regulatory environment for averting the inherent risks. As a consequence, authorities in China are taking steps to improve regulation and avert these risks. With respect to South Africa, the environment for shadow banking remains conservative, with minimal risks posed to the financial sector. Furthermore, in spite of its risks, shadow banking activities have helped to facilitate financial inclusion in the economy. Based on these findings, it is important that South Africa adopts a progressive approach to the regulation of shadow banking activities. It is important to ensure that there is a balance between facilitating financial inclusion and ensuring that shadow banking activities do not pose a risk to the financial system, through effective regulation. This calls for smart regulation that ensures that shadow banking activities are effectively regulated to minimise risk without stifling economic growth.
Research report in banking law submitted to the faculty of Commerce, Law and Management, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Masters in commercial and business law, Johannesburg, 2019